PERAN GURU SEBAGAI AGEN PERUBAHAN DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA PENDIDIKAN ABAD 21 - Moh Fadli; Sri Yuanita Talingansing; Fajri Ahmad; Asma D. Salam; Shelsea Olivia D. Djafar; Rendy S. Sambara (CV. ADIBA AISHA AMIRA, 2026)
This study aims to examine the role of teachers as agents of change in improving students’ learning motivation in 21st-century education. This study is important because technological developments and changes in learning patterns require teachers to be more adaptive, innovative, and oriented toward students’ needs. The research employed a qualitative approach using library research. Data sources were obtained from scientific journals, books, and academic articles relevant to the research topic. Data collection was conducted through documentation studies, while data analysis used content analysis techniques. The findings indicate that teachers play important roles as motivators, facilitators, innovators, and guides in the learning process. The implementation of active learning methods, student-centered learning approaches, and the use of educational technology were found to increase students’ participation and learning motivation. The study also found that limited facilities, lack of technological mastery, and differences in students’ characteristics remain challenges in implementing 21st-century learning. This study provides practical implications for teachers and educational institutions in developing more effective, interactive, and relevant learning processes in modern education.